A PSYCHOLOGY OF FAITH: MATT 27:54 IN THE LIGHT OF EXOD 14:30-31 - Viviano, Benedict T. (Revue biblique, 1997)
The fourfold structure of the psychology of coming to faith found in Exod 14:30-31 (see, see, fear, believe) provided a Mosaic/pentateuchal typology or model for the narrative presentation of the coming to faith of the centurion and the guards with him as described in Matt 27:54. La structure quadripartite de la psychologie de la foi naissante qui se trouve en Ex 14,30-31 (voir, voir, avoir peur, croire) a fourni un modèle typologique mosaïque pour la genèse de la foi chez le centurion et les gardes telle qu'elle est décrite en Mt 27,54.